Signals from On High and the Power of Growth Mindset: A Natural Field Experiment in Attracting Minorities to High-Profile Positions - Jeffrey A. Flory; Andreas Leibbrandt; Christina Rott; Olga B. Stoddard (Institute of Labor Economics (IZA), 2021)
We conduct a large-scale natural field experiment with a Fortune 500 company to test several approaches to attract minorities to high-profile positions. 5,000 prospective applicants were randomized into treatments varying a portion of recruiting materials. We find that self-selection at two early-career stages exhibits a substantial race gap. Importantly, we show that this gap can be strongly influenced by several treatments, with some increasing application rates by minorities by 40 percent and others being particularly effective for minority women. The heterogeneities we find by gender, race, and career stage shed light on the underlying drivers of self-selection barriers among minorities.
Keywords: J15; J16; C93; D22; 330; field experiment; experiment; labor; gender; race; diversity